Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kompensasi terhadap Kinerja Karyawan (Studi pada PT. Sai Apparel Industries) - Lukmanul Khakim; Sri Isnowati (Universitas Batanghari, 2023)
The purpose of this study was to determine the effect of work motivation, work discipline, compensation on employee performance at PT. SAI Apparel Industries. The population in this study were all employees of PT. SAI Apparel Industries, which has a total of 1000 employees. The sample in this study amounted to 110 employees. The sampling technique used was purposive sampling method. The analysis in this study is multiple linear regression analysis where hypothesis testing is done through the t test and F test. The results of this study show that (1) Work Motivation has a positive and significant effect on Employee Performance, (2) Work Discipline has a positive and significant effect on Employee Performance, (3) Compensation has a positive and significant effect on employee performance